ACTIVATING INTERNAL CONTROL PROCEDURES AND THEIR ROLE IN REDUCING THE RISKS OF INFORMATION TECHNOLOGY (AN APPLIED STUDY IN A SAMPLE OF IRAQI INDUSTRIAL - Rifaat Ibrahim Khudhair Shujari; Thaar Umran Mousa; Noor Nadhim Hameed AL-Jassam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The research aims to clarify what is the internal control and to clarify the concept, importance and risks of information technology in economic units as well as to explain the role of internal control procedures in reducing the risks of information technology, the following two hypotheses have been put forward: (1) There are many risks to which data and information are exposed in light of the use of Information technology, (2) The existence of effective internal control procedures will contribute greatly to preserving data and information in light of the use of information technology, and the research sample is represented by workers in the Iraqi industrial companies including administrators, accountants, auditors and financial analysts These companies are: the General Company for Electrical Industries, the General Company for Textile Industries, the General Company for Battery Industry and the General Company for the Dairy Industry, and in order to achieve the goals of the research and test its hypotheses, a set of statistical methods have been used such as the arithmetic mean, percentage, standard deviation, correlation coefficient and coefficient of variation, as the research has reached a set of conclusions was that the most important internal control is working on scaling risks in the iT environment through a set of procedures for sub-systems of its administrative control and operational control Waller Accounting Department.